Decreased Activity of Erythrocyte Catalase and Glutathione Peroxidase in Patients with Schizophrenia - Vladimir V. Djordjević; Jelena Kostić; Žilijeta Krivokapić; Dane Krtinić; Milica Ranković; Milan Petković; Vladan Ćosić (Medicina, 2022)
Background and Objectives: Catalase and glutathione peroxidase (GPx) are important antioxidant enzymes that break down hydrogen peroxide (H2O2) in order to control its intracellular concentration, thus enabling its physiological role and preventing toxic effects. A lack or disruption of their function leads to the accumulation of hydrogen peroxide and the occurrence of oxidative stress. Accumulating studies have shown that the activities of key antioxidant enzymes are impaired in patients with schizophrenia. Since the published results are contradictory, and our previous studies found significantly higher erythrocyte superoxide dismutase (SOD) activity in patients with schizophrenia, the aim of this study was to determine the activity of enzymes that degrade hydrogen peroxide in the same group of patients, as well as to examine their dependence on clinical symptoms, therapy, and parameters associated with this disease. Materials and Methods: Catalase and GPx activities were determined in the erythrocytes of 68 inpatients with schizophrenia and 59 age- and gender-matched healthy controls. The clinical assessment of patients was performed by using the Positive and Negative Syndrome Scale (PANSS). The catalase activity was measured by the kinetic spectrophotometric method, while the GPx activity was determined by the commercially available Ransel test. Results: Erythrocyte catalase and GPx activities were significantly lower (p < 0.001 and p < 0.01, respectively) in subjects with schizophrenia than they were in healthy individuals. Lower catalase activity does not depend on heredity, disease onset, the number of episodes, or disease duration, while GPx activity showed significant changes in patients who had more than one episode and in those who had been suffering from the disease for over a year. Significantly lower catalase activity was noted in the PANSS(+/−) group in comparison with the PANSS(+) and PANSS(−) groups. The lowest catalase activity was found in subjects who were simultaneously treated with first- and second-generation antipsychotics; this was significantly lower than it was in those who received only one class of antipsychotics. Conclusion: These results indicate the presence of oxidative stress in the first years of clinically manifested schizophrenia and its dependence on the number of psychotic episodes, illness duration, predominant symptomatology, and antipsychotic medication.